SECURING ACCESS CONTROL TO SECURITY RESTRICTED AREAS AT THE CARGO SECURITY CHECK POINT (SSCP) STAFF AT SULTAN MAHMUD BADARUDDIN II PALEMBANG INTERNATIONAL AIRPORT - Heliena, Frydean; Kardi; Adriansyah, Feri (Journal of Engineering and Transportation, 2023)
Abstract: Purpose - This research was conducted to meet the standards for implementing SSCP Cargo at Sultan Mahmud Badaruddin II Airport in Palembang. Security control activities for entrances to security areas are limited to SSCP Cargo and their implementation is still less than optimal. Design/methodology/approach - The research methodology uses descriptive qualitative research methods, namely by explaining and describing phenomena to display data results scientifically or as they are without any manipulation process. The author obtained data based on the author's observations and documentation. Findings - The author found that there were discrepancies in the implementation of standard operating procedures for Security Checks carried out by Aviation Security personnel, the ease with which people could enter restricted security areas without having an Airport PAS, and the presence of access control point doors that had inadequate security. This triggers a potential threat to aviation security. Research limitation/implication - The limitation of this research is that the research method using direct observation is less accurate and requires people around SSCP Cargo to also be asked for information as well as a security survey. Practical implication - Sultan Mahmud Badaruddin II Palembang Airport must improve flight security in the cargo area because of the potential for unlawful actions against people who carry out these activities in the cargo area. Originality/value - This research has never been written by researchers from any university.